Porous carbon with high capacitance and graphitization through controlled addition and removal of sulfur-containing compounds. (March 2015) - Zhou, Yao; Candelaria, Stephanie L.; Liu, Qian; Uchaker, Evan; Cao, Guozhong
Abstract: Highly porous carbon with high degree of graphitization was synthesized through the addition of sulfur containing precursors during the sol–gel processing and subsequent removal of sulfur oxide during activation processes. This porous carbon was subjected to activation in air for different periods of time; the sample with 1.5 h air activation demonstrated a specific capacitance of the single electrode of 120.4 F/g in organic electrolyte at a current of 0.5 A. The retention of capacitance was more than 94.0% after 2000 charge–discharge cycles. The effects of controlled air activation on the evolution of porous structure and an improved degree of graphitization are discussed and used to explain the improved electrochemical properties including both specific capacitance and cyclic stability of the resulting porous carbon. Graphical abstract: Highlights: High capacitance of 120.4 F/g and 95.7% retention. Release of gaseous sulfur oxide benefits the improvement of the degree of graphitization. Air activation process facilitates the development of pore structure.